Development and validation of scale assessing the preparedness of objective structured clinical examination in undergraduate competency based medical education - Yuvaraj Krishnamoorthy; Sivaranjini Kannusamy; Karthika Ganesh; Mahalakshmy Thulasingam; Subitha Lakshminarayanan; Sitanshu S Kar (Wolters Kluwer Medknow Publications, 2022)
Background: Formative assessments methods such as objective structured clinical examination (OSCE) are reliable and valid assessment tools employed under the competency-based medical education (CBME) curriculum. However, there was no uniform scale to assess the attributes of OSCE for any of the medical subjects. Hence, this study was done to develop and validate a scale to assess the attributes of OSCE and make sure that the intended objectives of the OSCE are achieved. Methods: The scale was developed using literature review and expert opinion. It consisted of 10 questions and response to these items was based on a 5-point Likert scale ranging from "strongly agree" to "strongly disagree." The final version was administered among 30 students undertaking survey community diagnosis (CD) posting during their third semester. Exploratory and confirmatory factor analysis was performed to validate the scale. Results: Two-factor structures were obtained with eigenvalues of 4.32 and 1.90. Factor 1 consisted of seven items (positively faced questions) accounting for 42.84% of the variance, whereas Factor 2 had the remaining three items (negatively faced questions) explaining 19.36% of the variance. Thus, together, the two factors explained 62.20% of the variance. Goodness-of-fit indices revealed good Comparative fit index (CFI) s of 0.90, Tucker Lewis index (TLI) of 0.87, and acceptable Standardized Root Mean Square Residua (SRMR) of 0.13. The reliability coefficient (Cronbach's alpha) for the scale was 0.81. Conclusion: This study develops and validates a scale that can be used universally for assessing the attributes of OSCE across all disciplines and in medical education institutes in India.